Case-control study of risk factors for abscess development following hepatitis B vaccination in children in Timor-Leste, 2024 - Mariano da Silva Marques; Filipe de Neri Machado; Marcelo Amaral Mali; Nevio da Costa Sarmento; Domingos Soares; Noel Gama Soares; Cristovão de Alexandria Barros; Livia Natalia Maria Guterres Babo; Armandinha A. da C. Silva; Evaliza Adão Mendonça; Natalia Jesus da Silva; Nazario Barreto dos Santos; et al. (PLoS ONE, 2026)
Background Hepatitis B vaccination is essential for preventing chronic hepatitis B infection and its long-term complications. In 2024, a high proportion of reported adverse events following immunization (AEFI) in Timor-Leste involved injection-site abscesses among infants who received the hepatitis B birth dose. This study aimed to explore potential factors associated with abscess formation to inform improvements in immunization practices. Methods We conducted a retrospective matched case-control study in public health facilities across 10 municipalities in Timor-Leste. Cases were infants aged <12 months with a clinically confirmed injection-site abscess occurring within 14 days after receiving the hepatitis B birth dose in 2024. Each case was matched 1:1 with a control by vaccination facility, approximate vaccination date, infant age group, and sex. Data on recipient characteristics, provider practices, vaccine handling, and cold chain management were collected through caregiver interviews, review of clinical and vaccination records, and facility assessments. Matched bivariate associations were evaluated using the exact McNemar test. Results None of the examined variables showed statistically significant associations with injection-site abscess formation; confidence intervals were extremely wide, reflecting the small sample size (12 pairs) and the very small number of discordant pairs (≤4 for all comparisons). Findings should therefore be interpreted as descriptive and hypothesis-generating only. Conclusions This exploratory matched case-control study did not identify any statistically significant risk factors for injection-site abscesses following hepatitis B birth-dose vaccination. Due to the very small sample size, inferential estimates were highly unstable; therefore, the findings should be interpreted as descriptive and hypothesis-generating rather than confirmatory. Despite these limitations, strengthening safe injection practices, appropriate multidose vial management, and adverse events following immunization (AEFI) surveillance systems remains critical. Larger prospective studies are needed to reliably investigate potential determinants of abscess formation.